EKSISTENSI MANGROVE DI DESA BELO LAUT, BANGKA BARAT, KEPULAUAN BANGKA BELITUNG DALAM PERSEPSI PEMBUDIDAYA KERANG DARAH - Ahmad Aji A Kurniawan; Ira Triswiyana; Ardiansyah Kurniawan (Journal of Aquatropica Asia, 2021)
Belo Laut Village has 3,337 ha of mangrove potential spread over three hamlet areas, namely Belo Laut, Tanjung Punai, and Sukal. On the muddy beaches around the mangroves, the community has developed extensive cultivation of blood clams (Anadara granusa). The existence of cultivation in mangrove areas also has the potential to affect the existence of mangroves in the area. For this reason, it is necessary to know the perception of shellfish cultivators on mangroves and the reality of the condition of mangroves in Belo Laut Village so as to provide an overview of the potential for mangrove destruction due to Blood Clam cultivation. Data were collected by interviewing shellfish farmers in Sukal and Tanjung Punai Hamlets. The production of blood clam cultivation has become a new source of economy in Belo Laut Village which is carried out by almost all family heads in Sukal and Tanjung Punai Hamlets. The community considers that the mangroves in Belo Laut village had not changed in quantity and there was no indication of their use other than for tourism. The perception and understanding of shellfish farmers not to disturb the mangroves were based on the protection of their main source of income as shrimp and crab fishermen.